Comparativo entre IEEE 802.11g e 802.11n - Leandro, Willian Andrukiu (2012)
Considering that modern life has led man to seek the technology, speed and security for the execution of their daily tasks or even for your leisure. What confirms that for many users, mobility is essential because they must be connected full time and it came to wireless technology. With the emergence of this new technology there was a need to create a standard, IEEE 802.11. More like all technology, had its developments to suit the needs that arose over time by companies and users. And also appeared empasses where some have created new standards of IEEE. Currently there are several patterns, but most equipment is 802.11g and 802.11n. And based on this given the work aimed at the comparison between the two patterns. Where was concluded that two patterns are the same, but one is intended to cover the needs of a home and an office or other organization.